DIATOMS FOR NANOMANUFACTURING - New Principles for Orientation and Immobilization - GREESHMA, NUTHALAPATI (My University, 2011)
Diatoms, unicellular micro-algae are one of the most common types of phytoplankton encased in unique cell walls made of silica (hydrated silicon dioxide) called frustules.* The cell wall is composed of biogenic silica extruded by the cell which is synthesized intracellular by polymerization of silicic acid monomers. Individual cells could manufacture highly accurate 3D structures in silica from nano meter to micro meter range. Diatoms create scores of very complex three-dimensional structures on a scale which would otherwise be content to create two-dimensional structures. The silica shell could be used as a template to produce a replica in other materials. In the Vinnova project “Genome based Manufacturing” we investigate how diatoms could be utilized to produce 3D micro-and nano-structures. Different methods to orient and immobilize the diatoms are investigated by us at Swerea IVF. Asymmetrical benthic diatoms such as “Surirella Sp” are used for the project. A marine biologist, Anna Godhe at Department of Marine Ecology, University of Gothenburg and a researcher, Anders Blomberg at Department of General and Marine Microbiology, University of Gothenburg are working with the characterization and principles to manipulate the genome of diatoms and to control the structure built by the algae, which is another part of the Vinnova project. Microstructure for orientation and immobilization of Diatoms: For the orientation and immobilization of the diatoms we designed a PDMS stamp for printing of organic and inorganic materials on glass substrate and a patterned glass plate for light illumination. The diatoms are attracted to light and the working hypothesis is that they will creep towards the light and reside on the illuminated spot. Motile diatoms move for a while and then slightly adhere to the surface. By understanding the chemotactic, phototactic and adhesion behaviors, we can get the diatoms to move into specified positions, say on a micro-patterned substrate, and then once they are in place convert them into organized arrays of nanotechnology components. Diatoms have the ability to make their movements directive and useful for them in the slightest way. Photosynthetic in nature, light is the primary energy resource, therefore, orientation and movement can be controlled by light-based mechanisms. Here we use patterns having 20 μm size spots at a distance of 200 μm to observe the motility of diatoms regulated by light source or nutrient. The aim is that the diatoms move to the patterned area, and when they are oriented according to the pattern, we immobilize them. As a result, 3D array of silicon is obtained which could be used for manufacturing of complex micro /nano-structures. In the microelectronics industry fabrication based on conventional 2-D layer-by-layer techniques can be replaced, and low-cost mass production of nanostructured devices with intricate 3-D shapes is possible.
Keywords: Materialvetenskap; Nanovetenskap och nanoteknik; Annan biologi; Övrig teknisk materialvetenskap; Materials Science; Nanoscience & Nanotechnology; Other Biological Topics; Other materials science